(untitled) (International Journal of Mathematics and Physics, 2014)
Computational fluid dynamics (CFD) becomes more and more reliable tool to analyze the furnace opera-tion under different conditions. This paper provides and overview of the current possibilities of 3D–Finite Volume tool FLOREAN developed at the Institute for Heat and Fuel technology TU Braunschweig. This program is used for simulations of combustion processes in industrial furnaces. FLOREAN has been applied for the calculation of a fur-nace chamber of Aksu power station fired with low grade coal of Ekibastuz (Kazakhstan). Distributions of different parameters such as temperature, fluid flow properties (velocities, pollutant substances such as CO, NOx) etc. are si-mulated. These simulations can be used to design furnaces, optimize furnace operation and minimize pollutant emis-sions.